Bat Cave Vulnerability Index 3.0 (BCVI-S): An integrative and scalable tool to prioritise bat caves for conservation - Krizler C. Tanalgo; Alice Catherine Hughes (Global Ecology and Conservation)
Assessing the state of aboveground ecosystems is often possible using remotely sensed data and subterranean systems are often left in the dark. Caves and subterranean habitats represent distinct ecosystems which harbour unique species but are sensitive to different pressures. Given the challenge of assessing many taxa, bats are ideal ecological indicators of caves and subterranean ecosystems, because they serve as keystone species that facilitate energy flow to other life forms inside caves. We calibrated the Bat Cave Vulnerability Index 3.0 (BCVI-S) and its indicators to optimise the scalability and applicability of the index in wider contexts by improving the calculations of Biotic Potential and the use of more standardised remotely sensed data to obtain Biotic Vulnerability based on landscape features. We demonstrated the application of the BCVI-S and the differences in cave priority levels in terms of Biotic Potential, Biotic Vulnerability, and overall priority level. The BCVI-S was more sensitive to the presence of rare and threatened species while balancing the priority level of caves with a hyperabundant population of common species. Simultaneously, the BCVI-S showed higher congruence with the commonly used biodiversity indices than the BCVI-L. More importantly, our calibrated BCVI-S allows users and assessors to easily integrate priorities at different spatiotemporal scales and consider other contexts of bat caves. The updated index is user-friendly and offers a comprehensive standard method for identifying key caves for conservation, which can be integrated into broader national objectives and strategies.